Kajian Pengetahuan dan Peminat Bermain Musik Sasandu dalam Kalangan Masyarakat Kabupaten Rote-Ndao - Katharina Kojaing; Stanislaus Sanga Tolan; Melkior Kian; Patricia Petrawati Saptono; Maria Marchindy Efliemsu Panir; Petrus Nahak (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2024)
Purpose: Sasandu is a traditional musical instrument typical of the Rote-Ndao people of NTT Province, and has become an icon of NTT province. However, the activeness of the people of NTT, especially the people of Rote, in playing sasandu music seems to be lacking. It is very rare to find performances playing sasandu music. This research aims to determine the knowledge and interest in playing sasandu music among the people of Rote-Ndao district. Method: The research method was a survey and interviews with 440 respondents from four categories, namely: teenagers, parents, village government officials and arts activists. Each category of respondents was 110 people each. Respondents were found in 110 villages, in 11 sub-districts throughout the Rote-Ndao Regency area. Each sub-district has a minimum of 5 villages. Results and Discussion: As a result of the research, data was obtained that all respondents knew about the sasandu musical instrument, had heard the sound of sasandu music, had watched people playing sasandu and knew that sasandu was an icon of the NTT province. All respondents also stated that they liked hearing the sound of sasandu music. In the aspect of those interested in playing sasandu music, respondents in the categories of teenagers, parents, village officials and music activists, who stated that they wanted to play sasandu music were 43.63%, 16.35%, 25.45% and 83.63% respectively. Conclusion: This category of respondents, those who stated that they had tried to practice playing sasandu music were: 14.54%, 5.45%, 5.45% and 21.81%. It was concluded that the respondents' knowledge of sasandu was high but their interest in playing sasandu music was low.